ChemInform Abstract: Rapid Microwave Preparation and ab initio Studies of the Stability of the Complex Noble Metal Oxides La2BaPdO5 and La2BaPtO5. Issue 19 (13th May 2014) - Misch, Lauren M.; Brgoch, Jakoah; Birkel, Alexander; Mates, Thomas E.; Stucky, Galen D.; Seshadri, Ram
Abstract The title compounds are prepared by rapid microwave‐assisted solid‐state synthesis using stoichiometric amounts of La2O3, BaCO3, and Pd(acac)2 or Pt(acac)2 (alumina crucible, 1300 W, 15—20 min).